O EDUCANDO DA EJA: DIFICULDADES E SUPERAÇÕES NA APRENDIZAGEM DE MATEMÁTICA FINANCEIRA - Silveira, Karla Beatriz Vivian (2007)
This study if it relates to a story of experience of qualitative purpose, that involved the development of a proposal of Education of Financial Mathematics, next to the pupils of the EJA, centered in the analysis of the difficulties and overcomings in the Learning of the Young and Adults of Average Ensino of the Escola Estadual de Educação Básica Francisco Brochado da Rocha Centro Integrado de Educação Pública, in São Sepé, RS, Brazil. The study it had for objective to search to understand as the methodology of Projects of Kilpatrick, combined with activities contextualized in the Cooperative subject, can contribute with the motivation, criticized, curiosity, sociability and the learning of Financial Mathematics, integrated to the Functions of 1º degree. This method made possible to carry through works in group and individual and, from them, to identify and to analyze the learning difficulties, as well as carrying through retaken of the explanations and the situationproblem that contributed in the overcoming of the presented difficulties. As result of this work, it could be evidenced a social experience, involving the learning, multiple abilities and are integrals known, opportunities for the exchanges of experiences. The great propellant of this experience was the COOPERATIVE subject. In it, a product that made them to trust its capacities to learn Mathematics, to discover and to create solutions, to defy, to consider and to assume, through the diverse knowledge was developed with the pupils, the consequences of its choices, supported for a mediating learning and the social and cultural, proportionate knowledge for the education for the work of the assembly of the Cooperative. One of the results of this work is the contribution for the development of practical pedagogical fellow creatures, which assist the pupils to learn to know and to understand its difficulties of learning, as well as its causes, to work them in the search of the overcomings.